Culture and Education in Lviv during the German Occupation - Krasiwski, Orest (Poznańskie Towarzystwo Przyjaciół Nauk, 2013)
This paper analyses the basic principles of German occupation policy in the Ukrainian lands, attitude of the occupying power to local people, investigates governing methods in occupied territories, the government policy on culture and education.
Keywords: Galicia; World War II; German occupation; education; literature; culture; fine art